HEMOGLOBIN IN RELATION TO BODY MASS INDEX AND SOCIOECONOMIC CHARACTERISTICS AMONG PREGNANT WOMEN - Minal Akram; Shahnai Basharat; Muhammad Mustafa Qamar; Ayesha Basharat; Tanveer Ahmed; Sheraz Saleem (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine whether the body mass index (BMI) and hemoglobin (HB) level are associated with socioeconomic strata among pregnant women belonging to different socioeconomic strata.